Формування ринкового потенціалу металургійних підприємств на основі оцінки використання їх людського капіталу - Фонарьова, Тетяна Анатоліївна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 "Економіка та управління підприємствами (за видами економічної діяльності)". Національна металургійна академія України, м. Дніпро. Національний технічний університет "Харківський політехнічний інститут", м. Харків, 2019. Дисертаційна робота присвячена удосконаленню і подальшому розвитку теоретичних положень, методичних підходів та науково-практичних рекомендацій з формування ринкового потенціалу металургійних підприємств на основі оцінки використання їх людського капіталу. Сформовано визначення поняття "ринковий потенціал підприємства", як можливості й ризики розвитку підприємства під впливом керованих та некерованих чинників ринку. На основі цього визначення запропоновано оціночний механізм капіталізації ринкового потенціалу підприємства, який включає: аналіз цільового ринку та визначення структури ринкового потенціалу; визначення загальних та специфічних характеристик його складових; вибір оціночного підходу: визначення вартісних та інтегральних показників (зокрема ринкової позиції), а також визначення ефективності капіталізації ринкового потенціалу (коефіцієнта капіталізації). Для обґрунтування та визначення майбутніх стратегічних перспектив розвитку підприємства сформовано оціночну базу ринкового потенціалу підприємства, яка складається з відповідних ресурсів – активів підприємства та враховує людський капітал, як один з активів, а також включає витрати та не фінансові показники діяльності підприємства. Визначено методичний підхід урахування та оцінювання людського капіталу підприємства. Для інформаційно-аналітичного забезпечення цієї діяльності розроблена форма облікового документу, інформація з якого, являється базою для формування управлінського балансу людського капіталу в системі управлінського обліку підприємства. На прикладі діяльності ПАТ "ЄВРАЗ – ДМЗ" встановлено, що сумарна недооцінка ринкової вартості підприємства з урахуванням накопиченої вартості людського капіталу склала 583 млн. грн. Сформовано блок-схему для аналізу чинників формування ринкового потенціалу металургійного підприємства та оцінки показників використання їх людського капіталу на основі якої, визначена інтегральна характеристика ринкового потенціалу – ринкова позиція підприємств сектору Металургпрому. Визначено динаміку вартісних показників людського капіталу на рівні різних секторів економіки, та проаналізовано тенденції трансформаційних процесів в гірничо-металургійному комплексі України, що впливають на ефективність використання людського капіталу металургійних підприємств і, як наслідок – на реалізацію їх ринкового потенціалу.

Dissertation for the degree of Candidate of Economic Sciences in specialty 08.00.04 – economy and management of the enterprises (by types of economic activity). – National metallurgical Academy of Ukraine, Dnipro, 2019. – National Technical University "Kharkiv Polytechnic Institute", Kharkiv, 2019. On the basis of the analysis of the nature and tendencies of the development of market potential research, the proposed author's is defined in which under the market potential of the enterprise are understood the opportunities and risks of the enterprise development under the influence of managed and unmanaged factors of the market. The author's conception of the evaluation mechanism by capitalization of the market potential of the enterprise is proposed, which includes: analysis of the industry market and determination of the structure of the market potential; determination of general and specific characteristics of market potential components; choice of valuation approach: determination of value and integral indicators (in particular market position), and determination of capitalization efficiency of market potential (capitalization ratio). In order to substantiate the relationship between "market potential" and "human capital" within the logical chain "human capital – capitalization – enterprise value – market potential", a quantitative characteristic, which determines the homogeneity of this chain, is considered to be the parameter "cost of capital", the analytical base of which built on enterprise capitalization methods. To take into account human capital, as one of the assets of the enterprise, human capital is included in the estimation base of the market potential. In order to improve the human capital appraisal toolkit, as an element of the enterprise market potential, the stages of development of the essence of the concept of human capital are investigated. Based on the conducted research, an approach has been developed in which human capital is considered as a share of the value of the enterprise and the differences of particular forms of capital, namely the economic form (a share that can be directly determined by the cost indicators) are taken into account; cultural – (share that is converted into economic capital in part – ability, human competence, etc.); social – (in the form of various social attributes – connections); symbolic – (the kind of capital that is recognized in society – prestige, reputation, honor, etc.). It is substantiated that individual human capital should be considered as the property of the employee, with the market price of his labor and income from the funds invested in its development by the enterprise and is the price paid by the enterprise for the possibility of using (borrowing) individual human capital and according to percent theory is defined as the proportion (percentage) of the principal. The dynamics of the basic human capital indicators at the sectoral level are determined, and the tendencies of transformation processes in the mining and metallurgical complex of Ukraine, which affect the efficiency of human capital utilization of metallurgical enterprises and, as a consequence, the realization of their market potential, are analyzed. The work deals with accounting of individual human capital by value indicators. For information support of accounting of the state and estimation of the human capital in work the forms of the accounting cards are offered, information from which, should be the basis for formation of the management balance of the human capital in the system of management accounting of the enterprise. On the example of the activity of PJSC "EVRAZ – DMZ" it is found that the total undervaluation of the market value of the enterprise taking into account the accumulated cost of human capital amounted to UAH 583 million. An explicit model of analysis of factors of formation of market potential of metallurgical enterprise and estimation of indicators of use of their human capital has been formed metallurgical complex). Using cluster analysis and a set of market potential indicators of the above group of enterprises, the influence of human capital cost indicators on the integral characteristic of market potential – the market position of a metallurgical enterprise among its closest competitors in the domestic market – was proved.
Formation of market potential of metallurgical enterprises on the basis of assessment of the use of their human capital
Keywords: автореферат дисертації; ринковий потенціал; формування; людський капітал; механізм капіталізації; індекс ефективності використання; ціна залучення; конкурентна позиція; market potential; formation; human capital; mechanism of capitalization; efficiency index of use; price of attraction; competitive position; 331.103.15:658.13